2021
DOI: 10.3390/ijerph18084284
|View full text |Cite
|
Sign up to set email alerts
|

Can Male Patient’s Age Affect the Cortical Bone Thickness of Jawbone for Dental Implant Placement? A Cohort Study

Abstract: Dental implants are among the most common treatments for missing teeth. The thickness of the crestal cortical bone at the potential dental implant site is a critical factor affecting the success rate of dental implant surgery. However, previous studies have predominantly focused on female patients, who are at a high risk of osteoporosis, for the discussion of bone quality and quantity at the dental implant site. This study aimed to investigate the effect of male patients’ age on the crestal cortical bone of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 33 publications
0
2
0
Order By: Relevance
“…At prosthesis delivery (T1), mean subcrestal positioning of implant platform was 1.49 ± 0.47 mm in Test group and 0.79 ± 0.44 mm in Control group. Considering mean cortical thickness in human jaws (1.07 ± 0.44 mm in the posterior mandible and 0.71 ± 0.27 mm in the posterior maxilla 56 ), at T1 the implant‐abutment junction was likely positioned at cortical level in Control group and subcortically in Test group. Finite element analyses showed that subcrestal placement decreases stress in the crestal cortical bone 57 .…”
Section: Discussionmentioning
confidence: 99%
“…At prosthesis delivery (T1), mean subcrestal positioning of implant platform was 1.49 ± 0.47 mm in Test group and 0.79 ± 0.44 mm in Control group. Considering mean cortical thickness in human jaws (1.07 ± 0.44 mm in the posterior mandible and 0.71 ± 0.27 mm in the posterior maxilla 56 ), at T1 the implant‐abutment junction was likely positioned at cortical level in Control group and subcortically in Test group. Finite element analyses showed that subcrestal placement decreases stress in the crestal cortical bone 57 .…”
Section: Discussionmentioning
confidence: 99%
“…Understanding them thoroughly requires explaining the relationship between their functions and forms. Skull bone thickness differs between the genders [3,4]. Generally, a female skeleton tends to be smaller and less durable than a male skeleton.…”
Section: Introductionmentioning
confidence: 99%